Evaluating Barriers on Biogas Technology Adoption in China: The Moderating Role of Awareness and Technology Understanding - Ali, Shahid; Yan, Qingyou; Irfan, Muhammad; Chen, Zhenling (Frontiers in Environmental Science, 2022)
Biogas technology adoption is a challenge in developing countries like China. The primary objective of this study is to explore the major issues for the farmers in adopting biogas plants. The sample size was identified through the snowball sampling method. A total of 51 respondents of biogas plant adopters participated in this study. The structured questionnaire was used to collect primary data through respondents. The formulated suppositions were assessed by the partial least square structural equation modeling (PLS-SEM). The results indicate that all independent variables are significant and positively correlated with adopting biogas technology, reducing energy crisis, and attaining cost-saving purposes. The results further indicate that the low-cost and clear policy positively and significantly attracts farmers to adopt biogas plants. The selected variables and their adopted moderation have a significant and positive impact on this conceptual model. The findings further indicate that major maintenance and day-to-day operations of biogas plants are expensive due to a lack of skilled operators, untrained or partially trained owners, and the unavailability of technicians. The results suggest that the government needs to plan a clear policy, provide short operations courses and technical support with skilled technicians to biogas plant owners, and launch a media campaign about maintenance to develop biogas plants.